Self-regulation in problem-based blended learning - Alfrista Novalia Putri; Much Fuad Saifuddin (Association for Scientific Computing Electrical and Engineering(ASCEE), 2024)
Self-regulation is pivotal for student success in the 21st-century learning landscape, enabling learners to effectively manage their academic goals and processes. This research investigates the impact of problem-based blended learning on students' self-regulation skills. A quasi-experimental design was employed, featuring a non-randomized control group. The experimental group was exposed to problem-based blended learning, while the control group experienced traditional face-to-face problem-based learning. The study involved 65 students from SMA Negeri 1 Prambanan, with self-regulation assessed through a closed questionnaire addressing nine key indicators. Data analysis revealed no significant difference in self-regulation between the control and experimental groups; however, the experimental group showed better outcomes. This group's higher performance in self-regulation was attributed to the flexible, interactive, and time-independent nature of blended learning, which fosters better time management, environmental structuring, and goal-setting among students. The findings underscore the potential of problem-based blended learning to enhance students' self-regulatory capacities, ultimately contributing to improved academic achievement and the development of essential 21st-century skills.